Effect of corrosive pollutants on Gram Production - Sapkota, Kamal Raj (Janapriya Journal of Interdisciplinary Studies, 2017)
Gram is important crop of Nepali and Indian farmers. Most of the people take gram as regular food. There are several edible food products prepared from gram. Gram is cultivated mostly in Birgunj (Parsa), Morang and Terai region. Recently in these states industrialization and infrastructure development work going very fast causing huge amounts of pollutants and particulate entering into the atmosphere. The purpose of this study is to explore the effect of corrosive pollutants on gram production and study tries to find the gaps of pH in the different areas. Growing urbanization and unplanned activities around the city area and River side have negatively affected the environment. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 61-64